Hiding in plain sight: a new species of bent-toed gecko (Squamata: Gekkonidae: Cyrtodactylus) from West Timor, collected by Malcolm Smith in 1924 - Kathriner, Andrew; Bauer, Aaron M.; O’shea, Mark; Sanchez, Caitlin; Kaiser, Hinrich (Zootaxa, 2014)
We describe a new species of bent-toed gecko from a single specimen initially collected in 1924 by Malcolm Smith on Timor Island in the Lesser Sunda Archipelago of Indonesia. Cyrtodactylus celatus sp. nov. is distinguished from all other congeners by the following combination of characters: small adult size; without spinose tubercles on the ventrolateral body fold and along the lateral margin of the tail; 16 longitudinal rows of tubercles at midbody; 42 ventral scales between the ventrolateral folds at midbody; no transversely enlarged, median subcaudal scales; 17 subdigital lamellae (seven basal + ten distal) under the fourth toe; no abrupt transition between postfemoral and ventral femoral scale series. The specimen is the earliest confirmed record of the genus Cyrtodactylus for Timor, and it is the first putatively endemic gecko species described from this island.